Use Greatest Common Factor to rewrite the expression:

(63+81)
=
(
+

1 answer

To rewrite the expression \( (63 + 81) \) using the Greatest Common Factor (GCF), we first need to find the GCF of 63 and 81.

  1. Find the GCF of 63 and 81:

    • The prime factorization of 63 is \( 3^2 \times 7 \).
    • The prime factorization of 81 is \( 3^4 \).

    The common factor is \( 3^2 = 9 \).

  2. Factor out the GCF:

    • We can rewrite \( 63 \) and \( 81 \) in terms of the GCF of 9:
      • \( 63 = 9 \times 7 \)
      • \( 81 = 9 \times 9 \)
  3. Rewrite the expression: \[ 63 + 81 = 9 \times 7 + 9 \times 9 = 9(7 + 9) \]

Thus, the expression can be rewritten as: \[ (63 + 81) = 9(7 + 9) \]